Um ventre chamado coração: o processo de adoção nas perspectivas do marketing macrossocial - Lima, Clara Amorim Pontes Correia (2020)
The present study aims to analyze alternatives to assist in reducing the imbalance in the adoption system guided by macro-social marketing. Based on the assumption that the current adoption process in Brazil is configured as a complex social problem, considering that currently in the National Adoption Register there are 9,640 children eligible for adoption, while there are 46,186 applicant families in the same register. Considering the discussions about the inefficiency of social marketing in such cases, given the focus too much at the individual level, we chose to use the emerging approach called macro-social marketing to analyze this systemic problem. To this end, an integrative review of the literature on macro-social marketing and a discussion on the adoption process in Brazil was carried out in order to serve as a basis for data collection. The methodology used will be the one suggested by Kennedy (2017) which has four steps: (1) developing an understanding of the situation, (2) creating conceptual models of the system, (3) debate of the map and conceptual models of the system with the parties stakeholders and (4) action. To this end, interviews were conducted using the thematic oral history technique with families that are in the process of adoption or who have already completed it. In-depth interviews were also conducted with the other actors in the adoption system, such as leaders of social projects, representatives of the judiciary and those responsible for the host institutions, among others. In parallel, a participant observation was carried out with the Study Group and Support for Adoption (GEAD-JP) in person and online. After being collected, these data were transcribed and analyzed through content analysis. The data were grouped into two dimensions called System and Analytical View and Involvement and subjectivity. Within these dimensions, the information was divided into categories called: system structure, system criticisms and failures, positive points and suggestions, meaning and motivation, the complexity of the action, efforts, engagement and institutional practices, and subjective issues. Based on the data collected, we found that the system is complex and interconnected in fact, and that there are several causes for the imbalance found. The barriers were identified and their possible causes were listed, so we developed proposals for macro-social marketing interventions and their respective responsible in order to reduce or solve them according to their levels. As an example, efforts to prioritize adoption processes, partnerships with the judiciary for a key role in the development and provision of interventions, campaigns that demystify abandonment and promote conscious delivery, and lectures in communities on the steps of conscious delivery and illegality direct adoptions. These interventions must be presented at GEAD-JP and later taken by the group to the Child and Youth Court, which presented itself as the main interaction of the system. Adoption is not commonly addressed with this marketing bias, which characterizes one of the work academic contributions. Macro-social marketing is also a recent literature that has been used for confusing and complex systems, such as adoption in Brazil. The study may contribute to the realization of campaigns that not only make the population aware of the cause, but also encourage the mobilization of society in favor of children in a sheltered situation. In academia, applying a macro-social approach expands horizons for understanding the adoption system in Brazil. The research can also serve as a source of research and information for professionals working with the cause of adoption, as well as for researchers in social marketing.